2009
DOI: 10.1016/j.meegid.2009.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Plasmodium falciparum populations between lowland and highland sites and antimalarial drug resistance in Western Kenya

Abstract: Human travel to malaria endemic lowlands from epidemic highlands has been shown to increase the risk of malaria infections in the highlands. In order to gain insight on the impact of human travel, we examined prevalence, genetic variability and population genetic structure of Plasmodium falciparum in asymptomatic children from one highland site and three surrounding malaria endemic lowland sites in western Kenya, using multilocus microsatellite genotyping. We further analyzed the frequencies of mutations at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 55 publications
8
25
1
Order By: Relevance
“…Compared to the pyrimethamine resistance, it is notable that there is a delay in the emergence and development of sulfadoxine resistance alleles in both areas. This observation supports the presumption that the pfdhps resistance takes place only after a substantial fraction of the population has been selected for pyrimethamine resistance (22,33,34), and it likely reaffirms the previous clinical finding that mutations in the pfdhfr gene plays a major role in the failure of SP treatment against falciparum malaria (35,36). Though the SP drug selection was assumed to act independently and differently on dhfr and dhps loci (37,38), the asymmetry in the selection pattern suggests a potential genetic linkage between the two loci across chromosomal boundaries during the coselection of the drug combination (22,31).…”
Section: Discussionsupporting
confidence: 82%
“…Compared to the pyrimethamine resistance, it is notable that there is a delay in the emergence and development of sulfadoxine resistance alleles in both areas. This observation supports the presumption that the pfdhps resistance takes place only after a substantial fraction of the population has been selected for pyrimethamine resistance (22,33,34), and it likely reaffirms the previous clinical finding that mutations in the pfdhfr gene plays a major role in the failure of SP treatment against falciparum malaria (35,36). Though the SP drug selection was assumed to act independently and differently on dhfr and dhps loci (37,38), the asymmetry in the selection pattern suggests a potential genetic linkage between the two loci across chromosomal boundaries during the coselection of the drug combination (22,31).…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, the significantly higher MOI in Anjouan may reflect a higher level of malaria transmission in the rainy and swampy sampled areas, where vector control has for a long time been impaired by recurrent island-specific political crises. The genetic diversities appeared lower on the archipelago than on most of the African continent ( 4 , 5 , 27 – 30 ), probably because of the geographic isolation of the islands and their lower malaria transmission levels that could limit effective parasite population sizes and outbreeding. However, genetic diversities remained higher than in Asia ( 5 , 6 , 12 , 13 ) and South America ( 5 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, previous MS studies have demonstrated that the number of alleles and diversity of alleles (heterozygosity) across various MS markers decrease with decreasing P. falciparum transmission (Anderson et al 2000; Leclerc et al 2002; Hoffmann et al 2003; Machado et al 2004; Bogreau et al 2006; Dalla Martha et al 2007; Zhong et al 2007; Bonizzoni et al 2009). Such decreases in genetic diversity are generally is attributable to both low endemicity and fewer opportunities for sexual recombination between genetically distinct parasites circulating in low transmission, resulting in linkage of markers across chromosomes (Conway et al 1997; Anderson et al 2000; Durand et al 2003).…”
Section: Introductionmentioning
confidence: 93%